INFLUENCE OF LOW-INTENSITY LASER IRRADIATION ON THE GLUCOSE LEVEL IN BLOOD OF HEALTHY SUBJECTS - A. N. Batyan (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Investigation of glucose level in blood of healthy subjects in the applications of low-intensity laser irradiation (LILI) of different wave-lengths has been conducted in the research work.